A Prospective Study on Hypertension-Revealing it to be a key factor for various Medical Complications, their Management and Prevalence in a Secondary Care Hospital - Sultana, Dr. Amreen; Fatima, Shaima; Sultana, Arham; Anum, Summaya; Ziya Uddin, Mohd (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: High blood pressure or HTN is a heterogeneous group of disorder characterized by a persistent increase in blood pressure due to the force of blood pushing against the blood vessel walls, which develops over time due to unhealthy lifestyle choices, lack of awareness accompanied by low levels of treatment and uncontrolled rates lead to mortality. Globally Hypertension (HTN) affects two-third of the population resulting in 10.4 million deaths annually. Despite several initiatives, the prevalence of HTN and its adverse impact on cardiovascular, renal, and cerebrovascular morbidity and mortality are globally increasing. Objectives: The objective of the study is to detect the adverse outcomes of uncontrolled hypertension and review the treatment patterns in the management of hypertension to reduce its further complications. To assess whether the higher prevalence of undiagnosed hypertension or poor adherence to antihypertensive therapy or both may explain the higher prevalence of hypertensive complications. Results: In the study, the prevalence of hypertension was found to be 46% among the patient population with males (52.5%) being more prevalent than females (47.5%). Among all age groups, individuals aged 50-69 years were highly affected. From the study, it was found that a greater number of patients fall in the category of stage-2 hypertension (38.75%) followed by hypertension crisis (28.75%), stage-1 hypertension (25%), and normal (7.5%). More patients with uncontrolled hypertension experienced cardiovascular complications (55%) when compared to cerebrovascular (27.5%) and renal (17.5%) complications. The choice of antihypertensive drugs used in the management were diuretics (43.75%), CCB (41.25%), ARB (37.5%), BB (32.5%), B+A (11.25%), ACEI (6.25%), CS (3.75%), and AAB (2.5%). The most commonly prescribed drugs in the study were Furosemide (11.25%), Telmisartan (11.25%), Amlodipine (7.5%), and Metoprolol (6.25%). Conclusion: The study concludes that most of the patients with uncontrolled hypertension were suffering from cardiovascular complications with least being affected by renal and cerebrovascular complications. A regular and moderate degree of physical activity in combination with good lifestyle choices may have a good impact on hypertension control thus preventing further complications. However, blood pressure control is obtained in some individuals, while in some blood pressure was still elevated after the drug management due to the presence of co-morbid conditions and poor lifestyle modifications.